THE EFFECT OF INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE IMPLEMENTATION QUALITY, CAPITAL STRUCTURES ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS INTERVENING VARIABLES IN BANKING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE PERIOD 2013 – 2017 - Sagala, Indah Cahya (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to analyse the effect of intellectual capital, the quality of the implementation of good corporate governance and capital structure that affects firm value with financial performance as an intervening variable on banking companies listed on the Indonesia Stock Exchange 2013-2017. The population in this study amounted to 34 companies using the saturated sampling method. Data testing methods used are multiple linear regression analysis and path analysis. Hypothesis research results indicate that partially, intellectual capital variable has a significant positive effect on firm value, the quality of implementing good corporate governance has a negative effect and is not significant on firm value, capital structure has no significant effect on firm value. Financial performance is able to act as an intervening variable between intellectual capital variables and firm value. Financial performance is not able to mediate the variable quality of the implementation of good corporate governance and capital structure to firm value in banking companies listed on the Indonesia Stock Exchange 2013-2017.